Biblioteka i książka w procesie rewalidacji dzieci ze specjalnymi potrzebami edukacyjnymi na przykładzie Miejskiej Biblioteki Publicznej Filii 13 w Kielcach = The role of books and the library in the rehabilitation process of children with particular educational needs - Iwańska, Katarzyna (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The needs, capabilities, and psycho-social expectations of handicapped people have been, and continue to be, variously perceived in their surrounding society. Now we are seeing a lot of positive changes. For disabled people, this means that they can ?switch? from passive vegetation and isolation to living actively among other people. In this article, we show the methods and forms of working with children with particular educational needs implemented at Branch No. 13 of the Kielce City Public Library. The goals of these bibliotherapeutic lessons were the following: to mobilize participants in terms of their social and cultural lives; to prepare them for using the library and its collections by themselves; to reduce the stress caused by developmental deficits; to enhance relations with their schools and their broader environment, and in so doing furnish them with some aesthetically rewarding experiences.
Keywords: dzieci ze specjalnymi potrzebami edukacyjnymi; biblioterapia; dzieci z niepełnosprawnością; rewalidacja niepełnosprawnych; biblioteka publiczna; children with special educational needs; bibliotherapy; children with disabilities; public library